Sensing with photoluminescent semiconductor quantum dots. (24th January 2019) - Chern, Margaret; Kays, Joshua C; Bhuckory, Shashi; Dennis, Allison M
Abstract: Fluorescent sensors benefit from high signal-to-noise and multiple measurement modalities, enabling a multitude of applications and flexibility of design. Semiconductor nanocrystal quantum dots (QDs) are excellent fluorophores for sensors because of their extraordinary optical properties. They have high thermal and photochemical stability compared to organic dyes or fluorescent proteins and are extremely bright due to their large molar cross-sections. In contrast to organic dyes, QD emission profiles are symmetric, with relatively narrow bandwidths. In addition, the size tunability of their emission color, which is a result of quantum confinement, make QDs exceptional emitters with high color purity from the ultra-violet to near infrared wavelength range. The role of QDs in sensors ranges from simple fluorescent tags, as used in immunoassays, to intrinsic sensors that utilize the inherent photophysical response of QDs to fluctuations in temperature, electric field, or ion concentration. In more complex configurations, QDs and biomolecular recognition moieties like antibodies are combined with a third component to modulate the optical signal via energy transfer. QDs can act as donors, acceptors, or both in energy transfer-based sensors using Förster resonance energy transfer (FRET), nanometal surface energy transfer (NSET), or charge or electron transfer. The changes in both spectral response and photoluminescent lifetimes have been successfully harnessed to produce sensitive sensors and multiplexed devices. While technical challenges related to biofunctionalization and the high cost of laboratory-grade fluorimeters have thus far prevented broad implementation of QD-based sensing in clinical or commercial settings, improvements in bioconjugation methods and detection schemes, including using simple consumer devices like cell phone cameras, are lowering the barrier to broad use of more sensitive QD-based devices.